Solar calcination at pilot scale in a continuous flow multistage horizontal fluidized bed. (1st September 2020) - Esence, Thibaut; Guillot, Emmanuel; Tessonneaud, Michael; Sans, Jean-Louis; Flamant, Gilles
Graphical abstract: Highlights: High quality lime was processed in a continuous flow pilot-scale solar fluidized bed. Feedstock mass flow rate varied in the range 14.5–25 kg/h and mean solar power was 55 kW. Calcite mass flow rate of 20 kg/h resulted in a degree of conversion of 95.2% Thermochemical and thermal efficiency of the reactor reached 17% and 29% respectively. Abstract: Calcination of limestone for lime production was successfully performed in the continuous flow mode on a daily basis in a fluidized bed indirectly heated by concentrated solar radiation. Industrial calcium carbonate feedstock was decomposed at the focus of the CNRS 1 MW solar furnace in a pilot-scale solar reactor operating at an average power of 55 kW. The reactor was a four-stage horizontal fluidized bed, irradiated on a front metallic wall of 1 m long and 0.4 m high. A novel aiming strategy was applied to reduce the hot spots on the irradiated wall. The conversion degree was analyzed as a function of the fluidization conditions (air mass flow rate) and the particle mass flow rate. This latter parameter varied in range (14.5 – 25 kg/h), and the highest conversion degrees were obtained at high fluidization velocity. The best result was obtained for a calcite mass flow rate of 20 kg/h, resulting in a degree of conversion of 95.2%, a BET surface area of the lime of 5.39 m 2 /g, and 17% and 29% thermochemical and thermal efficiencies of the reactor, respectively. This achievement corresponds to a particle mass flow rate three times higher than the current state of the art for solar calcination of lime.